Types of Figurative Language Found in White Swan Selected Song Lyrics - I Kadek Bayu Parmawan; Desak Putu Eka Pratiwi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Abstract This study is aims to find out and analyze types of figurative language in White Swan selected song lyrics on album Behind The Door. The objective of this research ware to find out types of figurative language and analyze their meaning. There are two theories that used in this research. The first theory is proposed by Knickerbocker and Raninger (1963) to analyze the types of figurative language. The second theory is proposed by Leech (1981) to analyze of the meaning. This study used descriptive qualitative method to analyze the data source. For the result there were six types of figurative language that find in White Swan selected song lyrics, such as: 4 data of simile (16,67%), 5 data of metaphor (20,83%), 2 data of synecdoche (8,3%), 1 data of metonymy (4,16%), 6 data of personification (25%), and 6 data of hyperbole (25%). Based on the result the types of figurative language that dominantly used in White Swan selected song lyrics is personification and hyperbole. Abstract This study aims to find and analyze the types of figurative language in the lyrics of selected songs from White Swan on the album Behind The Door. The object of this study is to find out the types of figurative language and analyze their meaning. There are two theories used in this study. The first theory was put forward by Knickerbocker and Raninger (1963) to analyze the types of figurative language. The second theory was put forward by Leech (1981) to analyze the meaning. This study uses a qualitative descriptive method to analyze data sources. The results show that there are six types of figurative language found in the lyrics of the selected White Swan songs, namely: 4 simile data (16.67%), 5 metaphor data (20.83%), 2 synecdoche data (8.3%), 1 metonymy data (4.16%), 6 personification data (25%), and hyperbole as many as 6 data (25%). Based on the results of the study, the dominant types of figurative language used in the lyrics of the selected White Swan songs are personification and hyperbole.